2000
DOI: 10.1002/(sici)1099-0844(200006)18:2<109::aid-cbf861>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antioxidant vitamins A, C, E and trace elements Cu, Se on CuZn SOD, GSH‐Px, CAT and LPO levels in chicken erythrocytes

Abstract: The biologically damaging effects of reactive oxygen species are controlled in vivo by a wide spectrum of antioxidant defence mechanisms. Dietary constituents of antioxidant vitamins and trace elements may play an important role in protecting against oxidant damage. The effects of supplementation of vitamins A, C, E and trace elements Cu and Se on the activities of antioxidant enzymes and lipid peroxide levels in chicken erythrocytes were investigated depend on the time. CuZnSOD activity and plasma Cu levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Supplementation with antioxidative vitamins (A, C, E) and mineral micronutrients (including Cu and Se) increased the SOD activity, but did not affect the catalase activity in chicken blood and enhanced glutathione peroxidase GPx in brain tissue (Aydemir et al., 2000). In our studies, the used diets significantly affected only selected antioxidant blood parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with antioxidative vitamins (A, C, E) and mineral micronutrients (including Cu and Se) increased the SOD activity, but did not affect the catalase activity in chicken blood and enhanced glutathione peroxidase GPx in brain tissue (Aydemir et al., 2000). In our studies, the used diets significantly affected only selected antioxidant blood parameters.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes protect the cell membrane against peroxidation by converting the reactive compounds to less harmful or harmless metabolites. The determinations of MDA concentrations and antioxidant enzymes activities are the major criteria concerning the severity of possible peroxidation, which takes place in cell membrane (Aydemir et al, 2000;Gokhan et al, 2004;Ozturk-Ureket al, 2001). The decrease in activities of these antioxidant enzymes proved that lead indeed induced generation of reactive oxygen species/free radicals leading to increase production of MDA which was much higher than the level which could be compensated by the cellular defense systems, thus these compounds may not be converted to less harmful or ineffective metabolites at the sufficient levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on the biological variability of both antioxidant defence mechanisms and (LPO) with ageing. Animal studies have shown that antioxidant enzyme levels in chicken erythrocytes and tissues are variable depending on the availability of antioxidants in the diet (Aydemir et al., 2000; Urek et al., 2001).…”
Section: Introductionmentioning
confidence: 99%